2003
DOI: 10.1590/s0080-62342003000200010
|View full text |Cite
|
Sign up to set email alerts
|

Violência conjugal: vivências expressas em discursos masculinos

Abstract: RESUMO

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0
9

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 0 publications
1
8
0
9
Order By: Relevance
“…Ela também pode se expressar na forma de ameaças, chantagens, xingamentos, proibições às amizades ou visitas a parentes, e por atos destrutivos, como jogar fora ou destruir documentos e objetos pessoais, além de matar animais de estimação. Geralmente, as relações violentas obedecem a uma lógica progressiva e cruel, que pode chegar ao extremo dos homicídios (DINIZ, et al, 2003). Vale dizer que homicídios seguidos de suicídios geralmente envolvem relações afetivas dessa ordem, são realizados por homens, e as vítimas são: ex-parceiras, parceiras, ex--namoradas, ex-esposas, namoradas e esposas (SÁ; WERLANG, 2007).…”
Section: Violência Conjugalunclassified
See 1 more Smart Citation
“…Ela também pode se expressar na forma de ameaças, chantagens, xingamentos, proibições às amizades ou visitas a parentes, e por atos destrutivos, como jogar fora ou destruir documentos e objetos pessoais, além de matar animais de estimação. Geralmente, as relações violentas obedecem a uma lógica progressiva e cruel, que pode chegar ao extremo dos homicídios (DINIZ, et al, 2003). Vale dizer que homicídios seguidos de suicídios geralmente envolvem relações afetivas dessa ordem, são realizados por homens, e as vítimas são: ex-parceiras, parceiras, ex--namoradas, ex-esposas, namoradas e esposas (SÁ; WERLANG, 2007).…”
Section: Violência Conjugalunclassified
“…Historicamente, a mulher tem sido vítima da violência conjugal, mas o estudo de Diniz et al (2003) apontou o outro lado desse tipo de violência. Os homens entrevistados pelo grupo de pesquisadores apontam a mulher também como agressora nas mesmas proporções que o homem dentro de suas relações conjugais.…”
Section: Violência Conjugalunclassified
“…Even though violence is associated with physical injuries, the phenomenon is not characterized solely by clinical gravity, but equally by the psychological and social impact on the victims. This is explained by the fact that they not always leave visible marks, as long as physical violence (5) is only one of the forms of conjugal violence expression.…”
Section: Introductionmentioning
confidence: 99%
“…Statistics show that physical and sexual violence is experienced at least once in women's life is alarming in countries such as Canada, where the rate of abused women between 18 and 64 years old is 32.2%; in Nicaragua, 73.3% of women between 15 and 49 years old suffer violent acts; in the north of London this rate is 53% (women aged 16 year); in São Paulo, 35.4% of women between 15 and 49 years are victims of this aggression and in the countryside of Pernambuco, the domestic violence case rate in women in the age group of 15 to 49 years is 46.5% (7) . Study performed with 50 men residing in a given community in Salvador showed that 80% of the interviewed males cited the occurrence of violence, expressed physically, sexually, emotionally and by destructive attitudes against property (5) . Another study carried out in the cities of Salvador, Recife and Aracaju showed that 47% of women alleged to be forced to have sexual intercourses; 32% were prohibited to make friends or work; 44% were kicked, slapped, punched or pushed; and 32% were called names (8) .…”
Section: Introductionmentioning
confidence: 99%
“…Muitas vezes nomeada como violência perpetrada pelo parceiro íntimo, ou violência de gênero, ou ainda violência marital, a violência conjugal contra a mulher passou a ser objeto de atenção social e científica a partir da segunda metade do século XX, concretamente na década de 1960 (Caridade & Machado, 2006;Diniz, Lopes, Gesteira & Gomes, 2003). Todavia, publicações científicas sobre este fenômeno se tornaram expressivas apenas na década de 1970 (Crachat, Prudence & Annieelm, 1975;Field & Field, 1973;Gilles, 1977;Heusser, 1978;Kimball, 1977;Saunders, 1977).…”
Section: Introductionunclassified